Approximate Fourier domain expression for Bloch–Siegert shift. Issue 1 (29th January 2014) - Turk, Esra Abaci; Ider, Yusuf Ziya; Ergun, Arif Sanli; Atalar, Ergin
<x xml:space="preserve">Abstract</x> Purpose In this study, a new simple Fourier domain‐based analytical expression for the Bloch–Siegert (BS) shift‐based B1 mapping method is proposed to obtain <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2xqbwg3v" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />|B1+|</alternatives> more accurately while using short BS pulse durations and small off‐resonance frequencies. Theory and Methods A new simple analytical expression for the BS shift is derived by simplifying the Bloch equations. In this expression, the phase is calculated in terms of the Fourier transform of the radiofrequency pulse envelope, and thus making the off‐ and on‐resonance effects more easily understandable. To verify the accuracy of the proposed expression, Bloch simulations and MR experiments are performed for the hard, Fermi, and Shinner–Le Roux pulse shapes. Results Analyses of the BS phase shift‐based B1 mapping method in terms of radiofrequency pulse shape, pulse duration, and off‐resonance frequency show that <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2xqbwg29" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />|B1+|</alternatives> can be obtained more accurately with the aid of this new expression. Conclusions In this study, a new simple frequency domain analytical expression is proposed for the BS shift. Using this expression, <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2xqbwg1r" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />|B1+|</alternatives> values can be predicted from the phase data using the frequency spectrum of the radiofrequency pulse. This method works well even for short pulse durations and small offset frequencies. Magn Reson Med 73:117–125, 2015. © 2014 Wiley Periodicals, Inc.